Monitoring greenhouse gas emissions at the WAY CARBON carbonic polygon through regenerative animal husbandry - R. H. Bekmurzaeva; N. M. Bulaeva (Юг России: экология, развитие, 2023)
Aim. To monitor the flows of climatically active gases at the carboxylic range of the A.A. Kadyrov Chechen State University through regenerative animal husbandry.Material and Methods. We have been studying the territory of the northern slope of the Khoysko-Makozhoy depression allocated for pasture areas from April 2022 to the present. Reconnaissance and field studies were carried out, data were collected and processed in key areas to assess the seasonal dynamics of CO2 emissions, temperature and soil moisture in key areas. Information that is freely available on the Internet was used.Results. The article describes the territory of the carbon polygon, which is 1054 hectares in extent at the time of writing. The territory is divided into sections: reference, moderate and intensive grazing (ET, UM, IN - respectively). Experimental data were obtained from landfill sites; the main greenhouse gases, soil temperature and moisture, microbiological and chemical analyzes of the soil.Conclusions. The studies initiated in 2022 have made it possible to develop methodological foundations for systemic conjugate monitoring of greenhouse gas emissions at a carbon landfill using regenerative animal husbandry.